Simulasi Aspek Aerodinamis Aliran Udara 2-D Pada Mobil Model Dengan Variasi Jarak Antar Model - Subekti, Aditya Abyansyah; Suryawan, Anak Agung Adhi; Karohika, I Made Gatot (Teknik Desain Mekanika, 2024)
Abstract Vehicles have now become an important part of life to live everyday life, and as a result of this, the increase in fuel oil consumption continues to grow. Fuel oil is decreasing every year because petroleum is a non-renewable energy resource. So efforts to save on fuel consumption in vehicles began to be tried. One of them is by efficiently using a car. There are many ways to do this, such as setting up car platoons. The basic role of the platoon in driving at medium-short distances between vehicles in joint arrangement produces a considerable reduction in the drag coefficient so that platoon arrangements between cars can get aerodynamic values and ultimately fuel consumption for cars is also more efficient. The fluid flow that flows on the vehicle body will cause aerodynamic forces, due to the distribution of pressure and shear stress on the surface of the vehicle body. Computational Fluid Dynamics is a part of aerodynamics where aerodynamic values are obtained through calculations. CFD is a more efficient alternative in tool design or research to determine the characteristics of a flow and its interactions. To find out this, the authors conducted a study using CFD with the 2-D flow method between car models that varied the speed and distance between cars to find out the comparison of the values of ???????? and ???????? between vehicle models. The results show that the closer and smaller the speed will get a significant car performance efficiency which can be seen from the comparison of the values of ???????? of 97.57% and ???????? of 96.54% between models. Keywords: Efficiency, Coefficient Drag, Coefficient Pressure, Aerodynamics, Computational Fluid Dynamics